Криптографічний протокол з часовим розкриттям у мережі рівноправних вузлів - Гончар, С.А. (Управляющие системы и машины, 2015)
Розглянуто основні положення криптографії з часовим розкриттям. Показано, що найбільш перспективним напрямом розвитку таких систем є еволюція методів з використанням третьої сторони – мережі рівноправних вузлів та bitcoin-схем. Наведено основні положення представленого протоколу: створення числового ключа, відправка повідомлення, створення нових блоків та транзакцій, а також механізм розшифрування даних. Рассмотрены основные положения криптографии с временным раскрытием. Показано, что наиболее перспективное направление развития таких систем – эволюция методов с использованием третьей стороны – сети равноправных узлов и bitcoin-схем. Приведены основные положения представленного протокола: создание числового ключа, отправка сообщения, создание новых блоков и транзакций, а также механизм расшифровки данных. The main principles of time-released cryptography is observed. It is shown that the evolution of methods using the third part person such as peer-to-peer network and "bitcoin" scheme is a promising way of the time-released crypto systems development. The basic provisions of the proposed protocol are: creating of numerical key, sending a message, creating a new blocks and transactions, and also data decryption mechanism. The article discusses the principles of new cryptographic protocol that implements the peer-to-peer network and bitcoin schemes to the time-released cryptography concept. The main propositions of time-released cryptography is observed. There are two methods of implementing time-release cryptography: the first is based on the need to perform certain calculations in a specific period of time (time-lock puzzles), and the second requires a third party (or central authority) to carry out the process of issuing some information to open an encrypted text in a certain period or time. The use of the third party, usually a timeserver, received significant development after the introduction of an identity base encryption since the early 2000s and reached its peak in 2008. However, the new technologies have recently emerged which allow to secure online transactions without relying on a central authority. The steps to create a peer-to-peer network and sending a message do not differ from those for regular messages in the above-mentioned network. The main difference is an specifying of the release time as one of the transaction parameters. At some period of time the key to decrypt messages is sent by any network user that first detects that it is time to decrypt the recipient message. The basis for the safety and accuracy of the time message transmission is that some members of the network sends the block with part of the key before release time, this block will be rejected by other members of the network as a result of the mechanism of its verification. The verification process involves checking of the release time of the message and the hash corresponding transaction. The feature of the created protocol is that due to "bitcoin" formed a chain-chart transactions that does not allow attackers to simulate customers, and to access to certain data network. Also this protocol provides for users a new possibility to improve network protection, because the server is not used, like in other existing time-released protocols.